2013
DOI: 10.1063/1.4825262
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanorod arrays for photocathode applications

Abstract: Highly sensitive superhydrophobic Ag nanorods array substrates for surface enhanced fluorescence studies Appl. Phys. Lett.Influence of substrate temperature on glancing angle deposited Ag nanorods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Lu et al demonstrated that sunlight could also be used for the reduction of silver ions to nanoparticles adsorbed on the surface of DNA [ 51 ]. Among all the templates, anodic aluminum oxide (AAO) is the most commonly used for nanowire synthesis [ 52 , 53 ]. In 2020, AAO templates were used to synthesize single crystalline AgNWs, as shown in Figure 2 e [ 54 ].…”
Section: Agnw Synthesismentioning
confidence: 99%
“…Lu et al demonstrated that sunlight could also be used for the reduction of silver ions to nanoparticles adsorbed on the surface of DNA [ 51 ]. Among all the templates, anodic aluminum oxide (AAO) is the most commonly used for nanowire synthesis [ 52 , 53 ]. In 2020, AAO templates were used to synthesize single crystalline AgNWs, as shown in Figure 2 e [ 54 ].…”
Section: Agnw Synthesismentioning
confidence: 99%
“…For the situation without PNF, the emittance of beam can be written as formula (10), which contains intrinsic thermal emittance and the part caused by roughness of the cathode. When the PNF is introduced, the emittance mainly contains three parts: the intrinsic thermal emittance, the emittance caused by roughness, and the emittance caused by plasmonic near field, which can be given by formula (11).…”
Section: Calculation and Analysis Of The Emittance Increased By Pnfmentioning
confidence: 99%
“…Because the same electron emissions are assumed in the two simulations, both of the intrinsic thermal emittances can be written as ε Intrisic . Combined the formula (10) and (11), the emittance caused by the plasmonic near field can be obtained by formula (12)…”
Section: Calculation and Analysis Of The Emittance Increased By Pnfmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Silver nanorod (Ag NR) array substrate fabricated by oblique angle deposition (OAD) technology 19 has attracted the attention of researchers because it showed signi¯cant advantages in the¯ne control over the geometric parameters, simple fabrication process, good sensitivity and high reproducibility. 20 These merits make Ag NR array a good candidate for the SERS-based sensing and imaging, such as the photocathode applications 21 and biomolecule detection. 22,23 The concerned research mainly aimed at improving the electromagnetic (EM) enhancement e®ect and the reproducibility of Ag NR array.…”
Section: Introductionmentioning
confidence: 99%